Folate-conjugated human serum albumin-encapsulated resveratrol nanoparticles: preparation, characterization, bioavailability and targeting of liver tumors - Bolin Lian; Mingfang Wu; Ziqi Feng; Yiping Deng; Chen Zhong; Xiuhua Zhao (Artificial Cells, Nanomedicine, and Biotechnology)
This work investigated the preparation of specific targeted drug delivery systems in cancer chemotherapy by folate conjugated human serum albumin nanoparticles encapsulated resveratrol (RES) nanoparticles (FA-HSA-RESNPs). FA was coupled to HSA, and RES was encapsulated in FA-conjugated HSA by high pressure fluid nano-homogeneous emulsification. The average particle size and polydispersity index of NPs prepared under optimal conditions were 102.1 ± 4.9 nm and 0.001. The drug capsulation efficiency and drug loading efficiency were 98.36 and 14.66%, respectively. The analysis of the results of the physical characterization showed that the RES was present in the FA-HSA-RESNPs in an amorphous state. In vitro drug-release study showed that the NPs can release the drug persistently and slowly. The inhibition rate of FA-HSA-RESNPs and RES was detected using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide method to be 110.8 and 157.2 μM, respectively. The targeting ability of the FA-HSA-RESNPs for the HepG2 cell was measured by fluorescein isothiocyanate-modified albumin techniques. The uptake rate of FA-HSA-RESNPs was higher than that of the original RES. By using near-infrared imaging, in vivo activity was labeled with Cy5 fluorescent FA-HSA-RESNP confirmed FA-HSA-RESNP tumor-targeting ability. The intravenous administration bioavailability of FA-HSA-RESNPs was about 5.95-fold higher than that of the original RES.